The use of Kinesio Taping in the treatment of pain and shoulder dysfunction in patients after stroke - Kręgiel, Anna; Iłżecka, Joanna (Journal of Education, Health and Sport, 2018)
Introduction. Stroke is an important medical problem. One of the most common complications associated with paresis or paralysis of upper limb after stroke is pain and shoulder dysfunction. Kinesio Taping action is physiotherapy. Objective of the work. The aim of the study was to determine whether Kinesio Taping has the effect of reducing the shoulder complex pain in patients after stroke and to evaluate whether its use improves upper limb function in these patients. Material and methods. The study included 100 patients after stroke. Application techniques tapes were made according to the method used in Kinesio Taping. The total time of treatment lasted for seven days continuously. Evaluation of the degree of disability of patients was performed according to the mRankin scale. The severity of pain was assessed using a visual – analog scale VAS and modified pain questionnaire Laitinen, and upper extremity function was examined using scales ASES and Brunnström. Results. The level of pain by visual - analog scale VAS and a pain questionnaire modified Laitinen decreased after 7 days of treatment, and after 2 weeks after treatment was increased, but to a level lower than the initial one. Evaluation of upper limb function using Brunnström scale and factor SSI (Shoulder Score Index) indicated to improve the functionality of the shoulder and upper limb as a result of the applied therapy. Conclusion. The use of Kinesio Taping may be helpful in reducing pain and improving shoulder complex upper limb function in patients after stroke.